Implementasi Model Manajemen POAC (Planning, Organizing, Actuating, Controlling) dalam Program “Sekolah Qur’an Keluarga” Berbasis Tafsir Tematik Q.S. Luqman - Nandipah Roa'zah; Muslimatun Diana Muazaroh; Diana Elfiyatul Afifah; Sukirno Sukirno; Moh.Agil Nuruzzaman; Supeno Supeno; Munahar Munahar; Fina Ni'matus Sa'adah (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2021)
The implementation of the POAC management model (Planning, Organizing, Actuating, Controlling) in Islamic educational programs effectively supports structured and value-based learning environments. In programs like the "Family Quran School" based on Thematic Tafsir of Q.S. Luqman, POAC facilitates systematic planning of curriculum and activities aligned with Islamic teachings, clear organization of roles and responsibilities, active mentoring and exemplary leadership, and continuous evaluation through monitoring and reflection. Studies in Islamic boarding schools and Quranic education institutions demonstrate that POAC enhances religious character development, teacher professionalism, and program quality by integrating Islamic values with modern management principles. Planning involves designing vision, mission, and thematic content; organizing ensures task delegation and collaboration; actuating emphasizes habituation and role modeling; and controlling includes regular assessments and behavioral monitoring. This model helps maintain religious identity while addressing contemporary educational challenges, fostering independent and moral character among students. Thus, POAC offers a practical and culturally contextualized framework for managing Islamic educational programs like the "Family Quran School" effectively